2016
DOI: 10.1371/journal.pone.0150070
|View full text |Cite
|
Sign up to set email alerts
|

Computational Characterization of Osteoporosis Associated SNPs and Genes Identified by Genome-Wide Association Studies

Abstract: ObjectivesGenome-wide association studies (GWASs) have revealed many SNPs and genes associated with osteoporosis. However, influence of these SNPs and genes on the predisposition to osteoporosis is not fully understood. We aimed to identify osteoporosis GWASs-associated SNPs potentially influencing the binding affinity of transcription factors and miRNAs, and reveal enrichment signaling pathway and “hub” genes of osteoporosis GWAS-associated genes.MethodsWe conducted multiple computational analyses to explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 40 publications
(44 reference statements)
0
30
0
1
Order By: Relevance
“…222 SNPs linked to osteoporosis GWAS-associated lead SNPs had also been identified by using LD information in the Caucasians population via HapMap website [9]. Moreover, we obtained 107 known osteoporosis GWAS-associated genes which showed significant connectivity among proteins.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…222 SNPs linked to osteoporosis GWAS-associated lead SNPs had also been identified by using LD information in the Caucasians population via HapMap website [9]. Moreover, we obtained 107 known osteoporosis GWAS-associated genes which showed significant connectivity among proteins.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, the osteoporosis GWAS-associated genes have also been analyzed with Protein-Protein Interaction (PPI) network analysis tool in the study of the osteoporosis GWASassociated SNPs associated by the online PPI tool named String. Combining with GO and pathway analysis, we found that the hub proteins associated and the Wnt signaling pathway were related to the mesenchymal stem cell differentiation and hormone signaling that was related to the metabolism of osteoporosis [9]. Finally, it was found that the osteoporosis GWAS-associated SNPs in special region of genes had longrange interaction signal with other locus by analyzing the long-range interaction of osteoporosis associated SNPs on GWAS3D [10].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Полногеномные исследования выявили дополнительные полиморфные локусы, ассоциированные с МПК, качеством кости и/или риском переломов. Влияние этих локусов может реализоваться через связывание транскрипционных факторов, микроРНК, активность сигнального пути Wnt и других внутриклеточных путей передачи сигнала, дифференцировку стволовых мезенхимальных клеток и остеоцитов [22,23].…”
Section: обсуждение основного результата исследованияunclassified
“…Multiple GWASs have shown that CCDC170 is one of the genes most strongly linked to BMD across populations[1315]. Recent study have found that multiple SNPs in CCDC170 are associated with BMD, including rs6929137, rs371804, rs3734805, rs6932260, rs6904261, rs6932603, rs9383935, rs9383589, rs3734806 and rs3757322[16]. The functions of most of these SNPs in vivo and in vitro remain unverified.…”
Section: Introductionmentioning
confidence: 99%